Sustaining Forests : A Development Strategy - World Bank (Washington, DC, 2013)
Forest resources directly contribute to the livelihoods of 90 percent of the 1.2 billion people living in extreme poverty and indirectly support the natural environment that nourishes agriculture and the food supplies of nearly half the population of the developing world. Forests also are central to growth in many developing countries through trade and industrial development. However, mismanagement of this resource has cost governments revenues that exceed World Bank lending to these countries. Illegal logging results in additional losses of at least US$10 billion to US$15 billion per year of forest resources from public lands. If captured by governments, these losses could support expenditures in education and health that will exceed current development assistance to these sectors. Forests also are central to maintaining the environmental commons. Nearly 90 percent of terrestrial biodiversity is found in the world's forests, with a disproportionate share in the forests of developing countries. Most of the carbon emissions of developing countries come from deforestation, which accounts for between 10 and 30 percent of global carbon emissions. Growing forests are a valuable resource not just for their timber and biodiversity values but also for their prospective value if a global market emerges for the sequestering of carbon from forests. A Forest Strategy for the Bank that can make an effective contribution to poverty reduction and environmental management is central to achieving the Millennium Development Goals (MDG). These goals include increasing school enrollment, reducing child and maternal mortality, expanding health services, eliminating gender disparities, and improving environmental management for sustainable development. This publication is accompanied by a CD containing background materials on how the World Bank's Forests Strategy was developed, including the stakeholder consultative process, as well as information on the role of forests in poverty reduction, economic development, and the provision of environmental services that helped to shape the strategy. World Bank safeguard policies relevant to forests and a short video highlighting the strategy's objectives are also included in the CD. The Appendixes, Notes, Boxes, Figures and Tables are included as Volume 2.